Improving Initial Condition in Coordination Failures - Dumlao, Luis F (Archīum Ateneo, 2024)
Given initial condition in a social system, we aim to introduce an individual’s reaction function that is a logistic function resulting in a logistic curve. With the use of stylized modelling and simulation, we show the following. First, while coordination may be a solution to solve coordination failures, improving the initial condition is an alternative and or a complementary solution. Second, moderate improvement in the initial condition leads to better, albeit inferior equilibrium. And third, significant improvement in the initial condition leads to positive feedback loop that leads to the first best, and permanent equilibrium. Thus, the key difference is whether the improvement in the initial condition is moderate or significant. This helps explain phenomena that occur, for example, in macroeconomics, global warming, credit markets, and organizational behavior.